Modern weapons and military equipment for issue 2-2024 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Russia’s Anti-Satellite Nuke Could Leave Lower Orbit Unusable, Test Vehicle May Already Be DeployedRussia has launched an anti-satellite weapon